Effect of Supports on Stability and Water Tolerance of Co-Beta Based Catalysts in NO-SCR by CH4 - Chen, Jiaqi; Chen, Shuwei; Li, Ruifeng; Zheng, Jiajun (Asian Journal of Chemistry, 2014)
The effect of supports on Co-Beta based catalysts was investigated by various characterizations and reactivity in the presence (2.5 % H2O) and absence of vapor. As UV-visible, XPS, NO-TPD and NO-IR reported, the BZZ(Beta/ZSM5) and BMZ(Beta/MOR) composite supports boost the dispersion of Co active metal and decreased the BE value of catalyst, with a better acidity and stronger adsorption capacity expressed. Under dry condition, stronger stability on CoH-BZZ upon aged for 140 h was described compared with the one on CoH-Beta and CoH-BMZ. Under wet condition, both CoH-BMZ and CoH-BZZ catalysts exhibited higher catalytic activity, when the maximum NO conversion was 45 % on CoH-BMZ or 37 % on CoH-BZZ compared with 23 % on CoH-Beta. However, they had higher depression of NO conversion than CoH-Beta did in the presence of vapor. The loss of the active sites and the migration of active sites from Co2+ to cobalt oxide lead the deactivation of the catalysts.